2008
DOI: 10.1038/ni.1640
|View full text |Cite
|
Sign up to set email alerts
|

The kinase p38α serves cell type–specific inflammatory functions in skin injury and coordinates pro- and anti-inflammatory gene expression

Abstract: p38 mitogen-activated protein kinase (MAPK) mediates cellular responses to injurious stress and immune signaling. Among the multiple p38 isoforms, p38α is the most widely expressed in adult tissues and can be targeted by various pharmacological inhibitors. Here we investigated how p38α activation is linked to cell type-specific outputs using mouse models of cutaneous inflammation. We showed that both myeloid and epithelial p38α can signal to evoke inflammatory responses, yet the mode of skin irritation determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
263
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 244 publications
(285 citation statements)
references
References 50 publications
22
263
0
Order By: Relevance
“…CREB is implicated in MKP-1 expression, as shown in this study and others [25,26,62]. CREB may be phosphorylated by kinases [53] that are induced by M-CSF, such as PI-3K [63], or PKA induced by LPS [64].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…CREB is implicated in MKP-1 expression, as shown in this study and others [25,26,62]. CREB may be phosphorylated by kinases [53] that are induced by M-CSF, such as PI-3K [63], or PKA induced by LPS [64].…”
Section: Discussionsupporting
confidence: 65%
“…For example, ERK5 induced phosphorylation of the transcription factor monocyte-specific enhancer binding factor 2c, whose activation increases c-Jun expression [60]. In relation to the phosphorylation of c-jun by JNK-1, this effect could be exerted through translocation to the nucleus [61], where JNK-1 phosphorylates c-Jun and thereby enhances its transcriptional activity [54].CREB is implicated in MKP-1 expression, as shown in this study and others [25,26,62]. CREB may be phosphorylated by kinases [53] that are induced by M-CSF, such as PI-3K [63], or PKA induced by LPS [64].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…MAPKs include ERK, JNK and p38 MAPK, and control a wide spectrum of cellular processes (Kim et al 2008a). Accumulating evidence indicated that MAPKs actively participated in the regulation of autophagic process (Peter et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In Parkinson’s and Lewy body diseases, human tissue study supports a role for ERK/MAPK in the regulation of autophagy (Jung et al 2010). In colorectal cancer cells, a novel cell type-specific role of p38α MAPK is found to control and mediate autophagy (Kim et al 2008a). Either autophagy or apoptosis has been found to be regulated by JNK-mediated Bcl-2 phosphorylation (Kim et al 2008b).…”
Section: Discussionmentioning
confidence: 99%